Analisis Perbandingan Kinerja Keuangan pada PT Aneka Gas Industri Tbk Sebelum dan Sesudah Go Public - Aurellia Catra Ratnanggadi; Banter Laksana; Dadang Hermawan (Indonesian Journal of Economics and Management, 2021)
The purpose of the study is to find out there is a difference in financial performance of PT Aneka Gas Industri Tbk before and after Go Public during the period of 2014-2018. The data used in this research is quantitative data. This research is a comparative study with a quantitative approach. The data analysis method used was ratio analysis and paired-t test using the SPSS 24 application. The results of the study is the financial performance of PT Aneka Gas Industri Tbk through the ratios: CR, QR, ROI, ROE, DAR, DER and TATO before and after going public is not significant different.